Making the Case for Counsellor Education Accreditation in Canada: A Cross-Jurisdictional Review of Emerging Trends in the Pre-Service Training of Counsellors and Related Mental Health Professionals - Borgen, William; Robertson, Sharon; Caverley, Natasha; Patterson, Pamela (Canadian Journal of Counselling and Psychotherapy, 2021)
The Council for Accreditation of Counsellor Education Programs recognizes quality assurance of master’s-level counselling programs in Canada. Accreditation is important to the pre-service training of counsellors and psychotherapists who are preparing to enter into practice after graduation. This article identifies trends in counsellor education accreditation from a national perspective—ranging from changes in the regulatory landscape in Canada to the integration of social justice and diversity practices into programs of study while fostering innovative program design in times of fiscal restraint within Canadian post-secondary institutions. From an international perspective, this article highlights trends for counsellor education accreditation programs in the United States, Britain, and Australia. Overall, it is important to inform counsellor educators and personnel running counselling programs in Canada on counsellor education program development, with the goal of supporting quality standards for accrediting counselling programs in Canada while acknowledging professional mental health service regulations and public policy.